PENYELESAIAN SENGKETA IMPOR PRODUK HORTIKULTURA, HEWAN DAN PRODUK HEWAN ANTARA NEW ZEALAND DENGAN INDONESIA - Usak . (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
One of the functions of The WTO is to become an international trade dispute resolution forum for its member countries. International trade disputes may emerge when a country adopts certain trade policies that are contrary to the WTO principles and rules, or implementing trade policies that harm other countries. One such trade disputes has been involving Indonesia and New Zealand, when New Zealand considered Indonesia has hindered free trade by imposing quotas, minimum prices, import and import licensing period for horticultural products, animals and animal products from New Zealand. In May 2014 the two countries have held consultation through a meeting between the delegations of New Zealand and Indonesia as well as the Chairperson of the Dispute Settlement Body to discuss about the allegedly restrictive policy. However, the meeting did not bring any positive result. The case is an example of a conventional trade dispute in which the trade policy adopted by a country is considered to violate the principles of free trade by other countries. In this case, the author argue that Indonesia's policy to limit import of horticultural product animals and animal products from New Zealand are in accordance with the provisions of the WTO concerning measures of safeguards to protect local farmers in the country, and Indonesia as a developing country is entitled to the conditions contained in the provisions of Special And Differential Treatment (S & D). Keywords: importatation dispute, horticultura products, animal and animal products, World Trade Organization, New Zealand vs Indonesia